EKSISTENSI SEJARAH PENDIDIKAN ISLAM DI KALANGAN MAHASISWA GEN Z - Tanjung, Zulkifli (FKIP Universitas Al Washliyah Medan, 2025)
This study examines previously stated issues using a qualitative methodology with an emphasis on literature analysis. This method falls under the category of library research that looks at and addresses the primary questions regarding the existence of Islamic education history among students in generation Z. Numerous reading materials that are pertinent to the research issue, including books, scientific articles, journals, and other related publications, were used to gather data. Both deductive and inductive methodologies were used in the data analysis process. While the inductive approach is used to find new patterns based on the data discovered, the deductive approach is used to test preexisting theories and concepts. Researchers can better grasp the connection between the traits of generation Z and the Islamic Education History learning approach thanks to this analysis. The study's findings suggest that using creative and pertinent teaching strategies can enhance generation Z students' knowledge of Islamic education history. Student engagement has been shown to increase with the use of digital technology, including interactive learning apps, social media, and instructional videos. Furthermore, Islamic education history is crucial in promoting virtues like honesty, accountability, and reverence for Islamic scientific traditions. Therefore, the History of Islamic Education is not only pertinent in the present day, but it also plays a vital role in helping Generation Z students develop their sense of self as people who are aware of their religious and cultural heritage.